BIPOLAR AFFECTIVE DISORDER AND DISSOCIATION - COMPARISON WITH HEALTHY CONTROLS - Latalova, Klara; Prasko, Jan; Pastucha, Petr; Grambal, Ales; Kamaradova, Dana; Diveky, Tomas; Jelenova, Daniela; Mainerova, Barbora; Vrbova, Kristyna (Biomedical papers, 2011)
Introduction: According to recent findings, certain clinical symptoms of patients suffering from affective and anxiety disorder can be related to dissociation. The aim of our study was to examine if the level of dissociation in bipolar affective disorder differed from the level of dissociation in healthy volunteers.Methods: 41 patients suffering from bipolar disorder (51.2% females), and 198 healthy controls ( 71.2% females) were included in the study. The patients with bipolar affective disorder in remission were recruited from the Outpatient department of the Department of Psychiatry of the University Hospital Olomouc. They were psychiatrically assessed and the state of the disorder was evaluated by an experienced psychiatrist. Only patients in remission, evaluated as 1 or 2 points of clinical global impression - severity scale, were included in the study. All participants were assessed with the Dissociative Experiences Scale (DES).Results: There were no differences in the two groups in demographic variables like age, gender and education. Patients had a significantly higher mean score on the DES and pathological DES than healthy controls.Conclusion: Our results suggest that the level of psychological dissociation in bipolar affective patients is higher than in healthy controls.
Keywords: Bipolar disorder/Healthy controls/Dissociation/Onset of the disorder